Performance Evaluation of SVM Algorithm in Sentiment Classification: A Visual Journey of Wonderful Indonesia Content - Singgalen, Yerik Afrianto (STMIK Budi Darma, 2024)
This study addresses the research problem of understanding public sentiment towards tourism-themed content on YouTube, with a specific focus on